La documentazione territoriale tra innovazione e tradizione - Santarsiero, Domenico (GEOmedia, 2010)
Land documentation between tradition and innovation Microgeo and Geosoft organized a workshop that was attended by many professionals of different nature and extraction. Topography and spatial asset detectors, cartographers and producers of spatial data as operators in the field of aerial photogrammetry and simple insiders as who wrote.